E-LEADERSHIP DALAM PERSPEKTIF KEPEMIMPINAN SPIRITUAL ISLAM: PENGARUHNYA TERHADAP PENINGKATAN MUTU PENDIDIKAN - Ambo’ Dalle, Abd. Rahman; Maulida, Rizky; Zaini, Rifan; Sutrisno, Sutrisno; Susilawati, Samsul (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2025)
This study aims to analyze the influence of e-leadership and Islamic spiritual leadership on the quality of education in madrasah. This study used a quantitative approach with an explanatory research design, involving 84 madrasah teachers as samples. The data analysis technique used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results showed that e-leadership has a significant effect on Islamic spiritual leadership and education quality. In addition, Islamic spiritual leadership is also proven to have a positive and significant influence on the quality of education. Other findings show that e-leadership has an indirect positive impact on education quality through Islamic spiritual leadership. Thus, the integration of e-leadership and Islamic spiritual leadership plays an important role in improving the quality of education in madrasah. This reflects that technology-based leadership development and spiritual values can create an educational environment that is more effective and adaptive to the development of the digital era. The implications of this research emphasize the need for madrasah leaders to implement a balanced leadership strategy between the use of technology and Islamic spiritual values in order to form graduates who are superior, have character, and are ready to face global challenges.